The politics of parody : a literary history of caricature, 1760-1830 - Taylor, David Francis (The Lewis Walpole series in eighteenth-century culture and history, 2018)
An original take on literary history that uses visual satire to explore literature's importance to eighteenth-century political culture The first in-depth analysis of the relationship between literature and visual satire in eighteenth-century Britain, this engaging study explores how the works of Shakespeare, Milton, Swift, and others were taken up by caricaturists as a means of helping the public make sense of political issues, outrages, and personalities. In a fascinating and novel approach to literary history, Taylor explores how great texts, seen through the lens of visual parody, shape how we understand the political world